(Studi Kasus Mengenai Arus Komunikasi Organisasi Dalam Membangun Semangat Kerja Pegawai Di Dinas Komunikasi Dan Informatika Kota Sukabumi): Studi Kasus Mengenai Arus Komunikasi Organisasi Dalam Membangun Semangat Kerja Pegawai Di Dinas Komunikasi Dan Informatika Kota Sukabumi - Gerry Rizky Andrean Supit (Jurnalika : Jurnal Ilmu Komunikasi, 2023)
Organizational communication is one aspect that exists within the organization and talks about the transfer of information from a leader to subordinates, this is indicated by the existence of a communication flow consisting of vertical communication, horizontal communication, and diagonal communication, in order to achieve the goals of the organization it must be good communication carried out by employees so that the morale that is built will be higher. The work spirit that is built by all employees affects work productivity. The problem examined in this study is how the implementation of organizational communication flows is carried out by superiors to subordinates, subordinates to superiors, horizontal communication and diagonal communication occur, this is related to the four communication flows proposed by Ha-run (2008: 45) and various obstacles found in the implementation of organizational communication. The aim is to find out the implementation of the communication flow proposed by Harun. This research uses a qualitative case study approach. Based on the data obtained in the field, it shows that not all organizational communication delivery flows are not implemented properly, entirely, only two streams are mastered, namely vertical and horizontal communication, while diagonal communication flows in media channels cannot be seen to be used properly so that even when used the result is less effective and this has an impact on morale which should be high to be less than optimal.